Provider Staffing Effect on a Decision Aid Intervention - Ersek, Mary (Clin Nurs Res, 2013)
This study examined the association between Nurse Practitioner (NP) and Physician Assistant (PA) staffing in nursing homes and the effect of a decision-aid regarding feeding options in dementia on the frequency of surrogate- provider discussions and on surrogates’ decisional conflict. We compared these outcomes for facilities that had no NP/PAs, part-time only NP/PA staffing, and full-time NP/PA staffing. The sample included 256 surrogate decision-makers from 24 nursing homes. The decision aid was associated with significant increases in discussion rates in facilities with part-time or no NP/PA staffing (26% v. 51%, p <.001 and 13% v. 41%, p < .001, respectively) and decreases in decisional conflict scores (−0.08 v. −.47, p = .008 and −0.30 v. −.0.68, p = .014, respectively). Sites with full-time NP/PA staffing had high baseline rates of discussions (41%). These findings suggest that the decision aid and full-time NP/PA staffing can enhance surrogate decision-making in nursing homes.